Economics and hermeneutics - Lavoie, Don, 1951- (Routledge, 1990)
Economics and Hermeneutics looks at the ways that hermeneutics might help economists address problems such as entrepreneurship, price theory, rational expectations, monetary theory, welfare economics, and economic policy.